2010
DOI: 10.1051/0004-6361/200913356
|View full text |Cite
|
Sign up to set email alerts
|

Estimating the phase in groundbased interferometry: performance comparison between singlemode and multimode schemes

Abstract: Aims. We compare the performance of multi and singlemode interferometry for estimating the phase of the complex visibility. Methods. We provide a theoretical description of the interferometric signal that enables us to derive the phase error with detector, photon, and atmospheric noises, for both multi and singlemode cases. Results. We show that despite the loss of flux which occurs when the light is injected in the singlemode component (i.e. singlemode fibers, integrated optics), the spatial filtering propert… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
12
0

Year Published

2011
2011
2019
2019

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 9 publications
(12 citation statements)
references
References 30 publications
0
12
0
Order By: Relevance
“…Consequently, significantly brighter objects must be observed, which affects the co-phasing limiting magnitude of the interferometer. Theoretical studies of the singlemode flux in partial AO correction (Tatulli et al 2010) confirm that this behaviour is observed on the VLTI. They explain in part why AMBER under-performed with its H-band FINITO fringe tracker (Bonnet et al 2006;Mérand et al 2012).…”
Section: Introductionmentioning
confidence: 69%
“…Consequently, significantly brighter objects must be observed, which affects the co-phasing limiting magnitude of the interferometer. Theoretical studies of the singlemode flux in partial AO correction (Tatulli et al 2010) confirm that this behaviour is observed on the VLTI. They explain in part why AMBER under-performed with its H-band FINITO fringe tracker (Bonnet et al 2006;Mérand et al 2012).…”
Section: Introductionmentioning
confidence: 69%
“…As shown in Fig. 6 of Tatulli et al (2010), D = 4r 0 with tip/tilt correction leads to a mean Strehl (or coupling efficiency) of |ρ i | ∼ 25%, and therefore significant flux dropouts. Instead, at D = 2r 0 with tip/tilt correction, the mean Strehl increases to |ρ i | ∼ 65%, and the flux dropouts are significantly reduced, which improves the sensitivity of the array, relative to the telescope size 2 .…”
Section: Limiting Magnitudementioning
confidence: 89%
“…A coupling of 100% can virtually be reached, limited only by the size of the mode matching optics. This mode matching approach removes the small low-flux phase estimation disadvantage of single-mode over multi-mode recombination identified in Tatulli et al (2010). Once the light is injected into the fibre at the telescope focus, the fundamental mode can virtually be preserved all the way to the cophaser and science instrument.…”
Section: Modal Transportmentioning
confidence: 99%
“…The fiber coupling efficiency has been studied for almost thirty years (Shaklan & Roddier 1988;Ruilier & Cassaing 2001;Meimon et al 2013) but mainly in the case of good AO correction. The case of low AO correction has only been theoretically studied (Tatulli et al 2010). So we need to characterize it in practice in order to secure the expected performance at this AO regime.…”
Section: On-sky Coupling Efficiencymentioning
confidence: 99%